American Ornithologists' Union records - American Ornithologists' Union
Four volumes (1,200 pages) containing minutes of meetings, bylaws, lists of U.S. and foreign members, and treasury reports. Includes material relating to bird protection and the union's journal The Auk.
Collection material in English.
Keywords: Auk; Birds -- Conservation; Ornithology -- Periodicals; Ornithology -- Societies, etc